Integrasi Program Rumah Baca Sang Petualang untuk Meningkatkan Kesejahteraan Masyarakat Wonogiri - Miswanto Miswanto; Ely Masykuroh; Shinta Maharani (Institut Agama Islam Negeri Ponorogo, 2024)
The issue of poverty is a major topic of discussion on sustainable development in Indonesia. The Central Statistics Agency (BPS) stated that the poor population was at 9.57 percent or equivalent to 26.36 million people. Another problem is the high unemployment rate. According to BPS, the percentage of open unemployment rate (TPT) reached 5.45 percent. Low level of education is one of the causes of the problem. In addition, employment is not proportional to the population. Skills of individuals and society need to be improved. One of the containers as a place of empowerment is the Reading GardenCommunity (TBM). Of the many TBMs in Indonesia, they tend to focus on empowerment programs in the field of education. This study analyzes the implementation of empowerment programs at Rumah Baca Sang Petualang in Wonogiri and its impact on the welfare of the local community. A qualitative approach was used in this study to explore information related to the integration of empowerment programs and involvement from various parties who play a role in it. The source of this research is from interviews with founders, administrators, members and communities who are part of the empowerment process. The results of this study, the integration of empowerment programs used is a combination of empowerment programs in the field of education, empowerment of small and medium enterprises, empowerment in the field of animal husbandry and empowerment in the field of handicraft business. The integration of applied programs has supporting and inhibiting factors. The supporting factors in question are the role of the government, the role of the private sector and supporting regulations. The inhibiting factors are public awareness, limited infrastructure and limited resources. The impact of integrating empowerment programs can change people's mindsets, create non-formal education, create business opportunities, increase community income and reduce negative environmental impacts. Of these effects do not contradict the maqashid al-sharia.